2013
DOI: 10.1002/chem.201203142
|View full text |Cite
|
Sign up to set email alerts
|

Sulfination by Using Pd‐PEPPSI Complexes: Studies into Precatalyst Activation, Cationic and Solvent Effects and the Role of Butoxide Base

Abstract: The activation of PEPPSI precatalysts has been systematically studied in Pd-catalysed sulfination. Under the reactions conditions of the sulfide and KOtBu in toluene, the first thing that happens is exchange of the two chlorides on the PEPPSI precatalyst with the corresponding sulfides, creating the first resting state; it is via this complex that all Pd enters the catalytic cycle. However, it is also from this same complex that a tri-Pd complex forms, which is a more persistent resting state. Under standard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…For C–S bond formation reactions conducted in the presence of the IPent ancillary ligand, the efficiency of the precatalyst was improved by changing the 3-chloropyridine ligand commonly used in the PEPPSI scaffold 51 (FIG. 1f).…”
Section: Pd-based Precatalyst Development Since 2012mentioning
confidence: 99%
“…For C–S bond formation reactions conducted in the presence of the IPent ancillary ligand, the efficiency of the precatalyst was improved by changing the 3-chloropyridine ligand commonly used in the PEPPSI scaffold 51 (FIG. 1f).…”
Section: Pd-based Precatalyst Development Since 2012mentioning
confidence: 99%
“…[1][2][3][4] This success has been aided by an increased understanding of the impact that the ancillary ligand has on the reactivity of the metal center. [1][2][3][4] This success has been aided by an increased understanding of the impact that the ancillary ligand has on the reactivity of the metal center.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] With high-reactivity palladium complexes in hand, researchers have turned their attention toward selectivity in couplings where one product is formed predominantly when more than one product is possible.O ne area of very high interest at present is the selective cross-coupling of secondary alkyl nucleophiles to aryl-and heteroaryl motifs as they lead to useful, structurally complex lead molecules for the discovery of new pharmaceutical agents [7] and materials for electronics applications. [2][3][4][5][6] Thenext step in the evolution of cross-coupling is to make the process more efficient and sustainable. [2][3][4][5][6] Thenext step in the evolution of cross-coupling is to make the process more efficient and sustainable.…”
mentioning
confidence: 99%
“…Other groups have also been active in this area, for instance, in 2013, Organ's group [50] reported the arylation of thiophenol with 2,6-dimethylbromobenzene (or sulfination of 2,6dimethylbromobenzene with thiophenol) using a variety of Pd-PEPPSI catalysts. The catalyst loading was fixed at 2 mol% and the reaction temperature from 40 to 80 ∘ C, giving very good yields in most cases.…”
Section: Migita Thioether Synthesis (C Ar -Sr Bond Formation)mentioning
confidence: 99%
“…The catalyst loading was fixed at 2 mol% and the reaction temperature from 40 to 80 ∘ C, giving very good yields in most cases. For example, the reaction with KOtBu at 70 ∘ C in toluene worked very well (insoluble in toluene), but those with Na (insoluble as well) or LiOtBu failed to work [50]. It was also observed that the less soluble the sulfide salt -which comes about by deprotonation of the sulfide -the better the reaction performance, and this can be controlled by the use of low dielectric solvents such as toluene [50].…”
Section: Migita Thioether Synthesis (C Ar -Sr Bond Formation)mentioning
confidence: 99%